WSGC Elijah High Altitude Payload 2012 Summer Team Final Report - Boldus, Brock; Comiskey, Patrick; Jones, Latisha; Mauk, Kaitlyn; Peterson, Ben; Weichart, Matthew (Proceedings of the Wisconsin Space Conference, 2012)
The 2012 Wisconsin Space Grant Consortium Elijah High Altitude Payload Team explored four different experiments this summer. We investigated the motion of the payload during flight, designed several systems for two cameras, utilized a magnetometer, and inspected the use of thermistors. Each experiment had numerous subcategories that resulted in more work than we had time for. Because of these unforeseen consequences, our team had to urgently attempt to make the deadline of the launch date. Through this haste, sections were overlooked; therefore we lost the cameras during flight and were not able to gather data from the magnetometer and thermistor experiments. However, this experience demonstrated a lot about the engineering process and working as a team. The internship taught us how to become better engineers through our mistakes and was an extremely worthwhile experience.Â